Management of premature ejaculation - a comparison of treatment outcome in patients with and without erectile dysfunction - Chia, Sing joo (International journal of andrology, 2002)
Summary This study evaluated the problem of premature ejaculation (PE) in patients treated for erectile dysfunction. The aim was to compare the efficacy of selective serotonin reuptake inhibitors (SSRIs) in the management of primary PE and PE associated with sildenefil treatment. Eighty‐seven patients with PE seen over a period of 17 months were recruited into this prospective study. They were categorized into two groups: primary PE (GPI) and PE in sildenefil‐treated patients (GPII). All patients recruited into GPII had erectile dysfunction (ED) that was successfully treated with sildenefil citrate for at least a year. Both groups of patients were given sertraline 50 mg 4 h before expected time of sex. The minimum follow‐up was 6 months. The ejaculation latency before and after treatment of the two groups were compared. The sexual satisfaction scores of the patients in the two groups were also sought and analysed. Twenty‐eight percent of patients with ED who were successfully treated with sildenefil developed PE. Subjects in group GPI were younger and have less comorbid factors than those in group GPII. There was no significant difference in the mean ejaculation latency for both groups (46 vs. 34.6 sec for GPI and GPII, respectively). However, there was highly significant difference in the ejaculation latency between the two groups after treatment with sertraline for 6 months (247.2 vs. 111.6 sec for GPI and GPII, respectively). There was also significant difference in the sexual satisfaction score for group GPI post‐treatment, but not for GPII. No significant side‐effect of sertraline was reported from patients in both groups. Successful treatment of ED could not assure sexual satisfaction. At least a quarter of sildenefil treated ED patients might develop PE which would continue to frustrate these patients sexually. While selective serotonin re‐uptake inhibitors (SSRIs) was effective in the management of primary PE, they were not as effective in patients with sildenefil corrected ED.